Negative plate and battery
By using carbon fiber to bind the expansion of silicon-based materials in the negative electrode sheet of lithium battery, the problem of reduced conductivity caused by the expansion of silicon-based negative electrode materials is solved, the circulation and rate performance of lithium batteries is improved, and the risk of lithium extraction is reduced, achieving low Impedance battery performance.
Patent Information
- Application Number
- CN202411357170.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
AI Technical Summary
The expansion of the silicon negative electrode material during charging and discharging leads to a decrease in conductivity, resulting in a deterioration in the circulation and rate performance of lithium batteries, and an increase in lithium evolution.
Using a negative electrode sheet design including a current collector, a first active material layer and a second active material layer, silicon-based material and carbon fiber are added to the first active material layer, and the ratio of the average length of the carbon fiber to the Dv50 of the silicon-based material is (0.61-1.83 ): Within the range of 1, the presence of carbon fibers restricts the expansion of silicon-based materials, improves conductivity and reduces the risk of lithium evolution.
The low impedance, high cycle performance and high rate performance of lithium batteries are achieved, reducing the risk of lithium evolution of the battery and improving the conductivity of the negative electrode sheet.
Smart Images

Figure CN119208534A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a negative electrode sheet, in particular to a negative electrode sheet and a battery, belonging to the field of secondary batteries. Background Art
[0002] With the continuous expansion and upgrading of the market demand for consumer electronics and power batteries, lithium batteries have become a commonly used power supply and energy storage device. At present, lithium batteries mainly include carbon negative electrode lithium batteries and silicon negative electrode lithium batteries. Among them, the energy density of silicon negative electrode lithium batteries is higher than that of carbon negative electrode battery modules, which can meet the needs of higher endurance.
[0003] However, the silicon negative electrode material has a high expansion rate during charging and discharging, which leads to the pulverization of the negative electrode active layer and reduces the conductivity of the negative electrode sheet, thereby increasing the internal resistance of the battery, resulting in poor battery cycle performance and rate performance, and increased lithium deposition in the battery.
[0004] Therefore, those skilled in the art are in urgent need of developing a negative electrode sheet with high conductivity that can take into account both the cycle performance and rate performance of the battery. Summary of the invention
[0005] The invention provides a negative electrode sheet, which has high conductivity, can make a battery present low impedance, and can make the battery have high cycle performance and rate performance.
[0006] The present invention provides a battery having low impedance, and high cycle performance and rate performance.
[0007] The present invention provides a negative electrode sheet, wherein the negative electrode sheet comprises a current collector, a first active material layer and a second active material layer, wherein the first active material layer is located between the current collector and the second active material layer; the first active material layer comprises a first active material and a conductive agent, wherein the first active material comprises a silicon-based material, and the conductive agent comprises carbon fiber;
[0008] The ratio of the average length of the carbon fiber to the Dv50 of the silicon-based material is (0.61-1.83):1; the Dv50 of the silicon-based material is 3.5-15 μm.
[0009] The negative electrode sheet as described above, wherein the ratio of the average length of the carbon fibers to the thickness of the first active material layer is (0.2-1.67):1.
[0010] The negative electrode sheet as described above, wherein the average length of the carbon fiber is 5-20 μm, the single fiber diameter is 100-170 nm, and the aspect ratio is (30-200):1.
[0011] The negative electrode sheet as described above, wherein the negative electrode sheet further comprises a primer layer, and the primer layer is located between the current collector and the first active material layer.
[0012] The negative electrode sheet as described above, wherein the second active material layer includes a second active material, and the second active material includes a silicon-based material and graphite.
[0013] In the negative electrode sheet as described above, the mass percentage of the carbon fibers in the first active material layer is 0.1-0.5%.
[0014] The negative electrode sheet as described above, wherein the conductive agent further comprises conductive carbon black, and the mass percentage of the conductive carbon black in the first active material layer is 0.5-3%;
[0015] And / or, the first active material layer further includes a binder, and the mass percentage of the binder in the first active material layer is 3.3-5.3%.
[0016] The negative electrode sheet as described above, wherein the silicon-based material comprises a silicon-carbon composite material, and the silicon-carbon composite material comprises a porous carbon matrix, silicon grains located in the pores of the porous carbon matrix, and a carbon layer located on the surface of the porous carbon matrix.
[0017] The negative electrode sheet as described above, wherein the carbon layer includes openings arranged corresponding to the pores of the porous carbon matrix.
[0018] The negative electrode sheet as described above, wherein the specific surface area of the silicon-carbon composite material is 0.5-10m 2 / g; and / or,
[0019] The particle size Dv50 of the silicon-carbon composite material is 6-15 μm; and / or,
[0020] The powder resistivity of the silicon-carbon composite material is 0.1-1000Ω·cm; and / or,
[0021] The silicon content in the silicon-carbon composite material is 30-75%.
[0022] The present invention provides a battery comprising the negative electrode sheet as described above.
[0023] The ratio of the average length of the carbon fiber in the negative electrode sheet provided by the present invention to the Dv50 of the silicon-based material is within a certain range, which can enable the carbon fiber to be in line contact with the silicon-based material, thereby improving the conductivity of the negative electrode sheet, and the presence of the carbon fiber can effectively restrain the expansion of the silicon-based material, inhibit the pulverization, breakage, or shedding of the negative electrode active material layer caused by excessive expansion of the silicon-based material, thereby avoiding the reduction of the conductivity of the negative electrode sheet, thereby improving the cycle performance and rate performance of the battery, and reducing the risk of lithium plating of the battery.
[0024] The battery of the present invention is prepared based on the above-mentioned negative electrode sheet, and the battery has high cycle performance and high rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a SEM image of the negative electrode sheet of Example 1;
[0026] Figure 2 is a SEM image of the negative electrode sheet of Example 1;
[0027] Figure 3 is a SEM image of the negative electrode sheet of Example 1;
[0028] Figure 4 This is the SEM image of the negative electrode sheet of Example 1.
[0029] Description of reference numerals:
[0030] 1- second active material layer;
[0031] 2-First active material layer. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The present invention provides a negative electrode sheet, which includes a current collector, a first active material layer and a second active material layer, wherein the first active material layer is located between the current collector and the second active material layer; the first active material layer includes a first active material and a conductive agent, wherein the first active material includes a silicon-based material, and the conductive agent includes carbon fiber;
[0034] The ratio of the average length of carbon fiber to the Dv50 of silicon-based material is (0.61-1.83):1; the Dv50 of silicon-based material is 3.5-15 μm.
[0035] The negative electrode sheet of the present invention comprises a current collector, a first active material layer and a second active material layer, wherein the first active material layer is located between the current collector and the second active material layer. The present invention does not limit the specific selection of the current collector, and the current collector can be selected according to actual needs, such as copper foil.
[0036] The first active material layer of the present invention includes a first active material and a conductive agent, wherein the first active material includes a silicon-based material and the conductive agent includes carbon fiber. The present invention does not limit other choices of the first active material, as long as it includes a silicon-based material. The present invention does not limit other choices of the conductive agent, as long as it includes carbon fiber.
[0037] The ratio of the average length of the carbon fiber of the present invention to the Dv50 of the silicon-based material is (0.61-1.83): 1, for example, the ratio is 0.61: 1, 0.7: 1, 0.8: 1, 0.9: 1, 1: 1, 1.1: 1, 1.2: 1, 1.3: 1, 1.4: 1, 1.5: 1, 1.6: 1, 1.7: 1, 1.8: 1 or 1.83: 1, etc. The Dv50 of the silicon-based material of the present invention is 3.5-15 μm, for example, Dv50 is 3.5 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or 13 μm, etc.
[0038] The present invention does not limit the composition of the second active material layer, which can be selected according to actual needs. For example, the second active material layer may include silicon-based materials or may not include silicon-based materials.
[0039] According to the above scheme provided by the present invention, the negative electrode sheet has high conductivity, which can make the battery have low impedance, high cycle performance and rate performance. The inventor analyzed this principle and believed that the reason may be that during the charging and discharging process of the battery, the silicon-based material in the first active material layer exerts high capacity, but with the expansion of the silicon-based material, the carbon fiber can be in line contact with the silicon-based material, improving the conductivity of the negative electrode sheet, and the presence of the carbon fiber can effectively restrain the expansion of the silicon-based material, inhibit the pulverization, breakage, or shedding of the negative electrode active material layer caused by the excessive expansion of the silicon-based material, thereby avoiding the reduction of the conductivity of the negative electrode sheet, improving the conductivity of the battery, and improving the cycle performance and rate performance of the battery, while reducing the risk of lithium precipitation of the battery. In addition, when the ratio of the average length of the carbon fiber to the Dv50 of the silicon-based material is within the above range, the carbon fiber can effectively restrain the expansion of the silicon-based material, avoid the excessive expansion of the silicon-based material causing the breakage of the carbon fiber, thereby maintaining close contact between the carbon fiber and the silicon-based material, improving the conductivity of the negative electrode sheet, reducing the impedance of the battery, and making the battery improve the cycle performance and rate performance.
[0040] Specifically, the average length of the carbon fiber of the present invention can be obtained by a transmission electron microscope (TEM) test method, comprising the following steps: subjecting the cross section of the negative electrode sheet to a TEM test, selecting 5-10 carbon fibers, testing their lengths, and taking the average value to obtain the average length.
[0041] The Dv50 of silicon-based materials can be obtained by laser particle size analyzer testing method.
[0042] In a specific embodiment, the ratio of the average length of the carbon fiber to the thickness of the first active material layer is (0.2-1.67): 1, for example, 0.2: 1, 0.3: 1, 0.4: 1, 0.5: 1, 0.6: 1, 0.7: 1, 0.8: 1, 0.9: 1, 1: 1, 1.1: 1, 1.2: 1, 1.3: 1, 1.4: 1, 1.5: 1, 1.6: 1 or 1.67: 1, etc. When the ratio of the average length of the carbon fiber to the thickness of the first active material layer is within the above range, the flexibility of the carbon fiber enables the carbon fiber to adhere to the surface of the silicon-based material, and the carbon fibers can be entangled with each other, thereby better inhibiting the expansion of the silicon-based material. At the same time, the carbon fiber can always be in close contact with the silicon-based material during the expansion of the silicon-based material, thereby better improving the conductivity of the negative electrode sheet, so that the cycle performance and rate performance of the battery are better.
[0043] Specifically, the thickness of the first active material layer of the present invention can be obtained by performing argon ion cutting on the cross section of the negative electrode sheet and testing it using a scanning electron microscope test method.
[0044] In a specific embodiment, the average length of the carbon fiber is 5-20 μm, for example, the average length is 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm, and the monofilament diameter is 100-170 μm, for example, the monofilament diameter is 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm or 170 μm, etc., and the aspect ratio is (30-200): 1, for example, 30: 1, 40: 1, 50: 1, 60: 1, 70: 1, 80: 1, 90: 1, 100: 1, 110: 1, 120: 1, 130: 1, 140: 1, 150: 1, 160: 1, 170: 1, 180: 1, 190: 1 or 200: 1, etc. The monofilament diameter of the present invention refers to the diameter of one carbon fiber. When the average length, single fiber diameter and aspect ratio of the carbon fiber are within the above ranges, it can ensure that after the silicon-based material expands, the carbon fiber can still be in close contact with the silicon-based material and will not break, thereby ensuring the low impedance of the negative electrode sheet, thereby improving the cycle performance and rate performance of the battery, and at the same time ensuring that the carbon fiber is evenly dispersed in the negative electrode active material layer to avoid excessive agglomeration of the carbon fiber, thereby improving the conductivity of the negative electrode sheet.
[0045] In a specific embodiment, the negative electrode sheet further includes a primer layer, which is located between the current collector and the first active material layer. The present invention does not limit the selection of the components of the primer layer, which can be selected according to actual needs. For example, the primer layer can be prepared from a carbon material. The provision of the primer layer of the present invention can enhance the adhesion of the first active material layer on the current collector, and avoid the shedding of the first active material layer caused by the expansion of the silicon-based material during the charge and discharge process, thereby ensuring the high cycle performance and rate performance of the battery.
[0046] In a specific embodiment, the second active material layer includes a second active material, and the second active material includes a silicon-based material and graphite. When the second active material includes a silicon-based material and graphite, the addition of the silicon-based material in the second active material layer can improve the energy performance of the entire negative electrode sheet, while the proportion of the silicon-based material in the second active material layer decreases, and the graphite can improve the conductivity of the negative electrode sheet and can synergize with the carbon fiber to reduce the expansion of the second active material layer, avoid the pulverization and shedding of the negative electrode active material layer, and thus improve the cycle performance and rate performance of the battery.
[0047] In a specific embodiment, the mass percentage of carbon fiber in the first active material layer is 0.1-0.5%, for example, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%, etc. When the mass percentage of carbon fiber is within the above range, enough carbon fiber is attached to the surface of the silicon-based material to inhibit the expansion of the silicon-based material, and can ensure the contact between the carbon fiber and the silicon-based material, improve the conductivity of the negative electrode sheet, thereby reducing the impedance of the battery, so that the cycle performance and rate performance of the battery are better.
[0048] In a specific embodiment, the conductive agent further includes conductive carbon black, and the mass percentage of the conductive carbon black in the first active material layer is 0.5-3%, for example, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%, etc. Since the silicon-based material will cause the carbon fiber to produce an interaction force after expansion, causing the surface of the carbon fiber to wear, resulting in an increase in the internal resistance of the negative electrode sheet, when conductive carbon black is added to the first active material layer and its content is controlled, the increase in the internal resistance of the negative electrode sheet caused by the wear of the carbon fiber can be suppressed, thereby further reducing the resistance of the battery and improving the cycle performance and rate performance of the battery to a greater extent.
[0049] In a specific embodiment, the first active material layer also includes a binder, and the mass percentage of the binder in the first active material layer is 3.3-5.3%, for example, 3.3%, 3.5%, 4%, 4.5%, 5% or 5.3%. The binder of the present invention includes at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, and polyacrylic acid. The first active material layer of the present invention also includes a binder. The addition of the binder can make the carbon fiber, silicon-based material, conductive carbon black and other components contact more closely, further improve the conductivity of the negative electrode sheet, and can inhibit the powdering or shedding of the negative active material layer caused by the expansion of the silicon-based material, thereby greatly improving the cycle performance and rate performance of the battery.
[0050] In a specific embodiment, the silicon-based material includes a silicon-carbon composite material, and the silicon-carbon composite material includes a porous carbon matrix, silicon grains located in the pores of the porous carbon matrix, and a carbon layer located on the surface of the porous carbon matrix. The present invention can arrange silicon grains in the pores of the porous carbon matrix by deposition, by arranging silicon grains in the pores, and by forming a carbon layer on the surface of the porous carbon matrix, and the carbon layer can be shaped carbon or amorphous carbon. When the silicon grains expand, the interior of the porous carbon matrix can provide sufficient expansion space to prevent the overall structural deformation of the silicon-carbon composite material, and the carbon layer can constrain the outward expansion force of the porous carbon matrix during the silicon expansion process, ensure the structural strength of the silicon-carbon material, thereby avoiding the problems of cracking, pulverization, and shedding of the negative electrode active layer, and improving the cycle performance and rate performance of the battery.
[0051] In a specific embodiment, the carbon layer includes openings arranged corresponding to the pores of the porous carbon matrix. When the carbon layer is provided with openings, the wettability of the electrolyte to the negative electrode sheet can be improved, and the expansion performance of the silicon-based material can be reduced, thereby reducing the impedance of the battery and improving the cycle performance and rate performance of the battery.
[0052] In a specific embodiment, the specific surface area of the silicon-carbon composite material is 0.5-10m 2 / g, for example 0.5m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g or 10m 2 When the specific surface area of the silicon-carbon composite material is within the above range, the SEI film formed on the surface of the negative electrode active layer during the charge and discharge process is appropriate, which can reduce the impedance of the battery and improve the cycle performance and rate performance of the battery.
[0053] In a specific embodiment, the particle size Dv50 of the silicon-carbon composite material is 6-15 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm. When the particle size Dv50 of the silicon-carbon composite material is within the above range, the particle size Dv50 of the silicon-carbon composite material is appropriate, which can avoid the situation where the particle size is too small, which easily leads to an increase in the specific surface area of the silicon particles and an increase in side reactions, and can also avoid the situation where the particle size is too large, which easily leads to excessive expansion of the silicon particles, resulting in blocking of the pores of the porous carbon matrix and affecting the infiltration of the electrolyte, thereby improving the cycle performance and rate performance of the battery.
[0054] In a specific embodiment, the powder resistivity of the silicon-carbon composite material is 0.1-1000Ω·cm, for example, 0.1Ω·cm, 0.5Ω·cm, 1Ω·cm, 5Ω·cm, 10Ω·cm, 50Ω·cm, 100Ω·cm, 200Ω·cm, 300Ω·cm, 400Ω·cm, 500Ω·cm, 600Ω·cm, 700Ω·cm, 800Ω·cm, 900Ω·cm or 1000Ω·cm. When the powder resistivity of the silicon-carbon composite material is within the above range, the conductivity of the silicon-carbon composite material is high, which can improve the conductivity of the negative electrode active layer, thereby improving the cycle performance and rate performance of the battery.
[0055] In a specific embodiment, the silicon content in the silicon-carbon composite material is 30-75%, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or 75%, etc. When the silicon content in the silicon-carbon composite material is within the above range, it is possible to avoid excessive silicon content in the silicon-carbon composite material, which leads to excessive expansion of the silicon-carbon composite material and deformation of the overall structure of the silicon-carbon composite material, thereby avoiding cracking and pulverization of the negative electrode active layer, ensuring the energy of the silicon-carbon composite material, and improving the cycle performance and rate performance of the battery.
[0056] The present invention provides a battery comprising the negative electrode sheet, which has low impedance and exhibits excellent cycle performance and rate performance.
[0057] In a specific embodiment, the battery of the present invention further comprises a positive electrode sheet, an electrolyte and a separator, specifically:
[0058] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer arranged on the surface of the positive electrode current collector, wherein the positive electrode active layer includes a positive electrode active material, a conductive agent and a binder, wherein the positive electrode current collector is generally an aluminum foil, and the positive electrode active material is selected from lithium transition metal oxides, for example, LiCoO2, LiMn2O4, LiMnO2, Li2MnO4, LiFePO4, Li 1+aMn 1-x M x O2、LiCo 1-x M x O2、LiFe 1-x M x PO4、LiMn 1-x O4, M is selected from one or more of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V, Ti, B, F, 0≤a<0.2, 0≤x<1.
[0059] The conductive agent and the binder in the positive electrode active layer can be selected from conventional materials in the art.
[0060] The electrolyte is any electrolyte known in the art that can be used in batteries.
[0061] The diaphragm is a diaphragm known in the art that can be used in batteries and is stable to the electrolyte used, and can specifically include one or more of polyolefin, aromatic polyamide, polytetrafluoroethylene, and polyethersulfone. Further, the diaphragm includes one or both of polyethylene and polypropylene. In addition, the diaphragm can be obtained by stacking multiple layers of materials in sequence, for example, the diaphragm includes a polypropylene layer, a polyethylene layer, and a polypropylene layer stacked in sequence.
[0062] Hereinafter, the present invention will be further described in detail through specific examples.
[0063] Example 1
[0064] The method for preparing the negative electrode sheet provided in this embodiment comprises the following steps:
[0065] 1. First active material layer: Mix the first active material, conductive carbon black, carbon fiber, styrene-butadiene rubber, sodium carboxymethyl cellulose, and polyacrylic acid in deionized water at a mass ratio of 91:3:0.75:3:0.75:1.5 to obtain a first active material slurry;
[0066] The first active material includes 33% silicon-based material and 67% artificial graphite, the Dv50 of the silicon-based material is 8.9 μm, the average length of the carbon fiber is 10 μm, the average diameter of the monofilament is 120 nm, and the aspect ratio is 83.3:1;
[0067] 2. Second active material layer: artificial graphite, conductive carbon black, carbon fiber, styrene-butadiene rubber, sodium carboxymethyl cellulose, and polyacrylic acid are mixed in deionized water at a mass ratio of 96.9:0.5:3:1.3:1.3 to obtain a second active material slurry;
[0068] 3. The first active material slurry and the second active material slurry are uniformly coated on the copper foil in sequence by using double-layer coating technology, and the negative electrode sheet is obtained after drying and rolling;
[0069] Wherein, the thickness of the first active material layer is 27 μm, and the thickness of the second active material layer is 60 μm;
[0070] According to calculation, the ratio of the average length of the carbon fibers to the Dv50 of the silicon-based material is 1.12:1, and the ratio of the average length of the carbon fibers to the thickness of the first active material layer is 0.37:1.
[0071] Example 2
[0072] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that in Embodiment 1, except that the Dv50 of the silicon-based material is 5.9 μm. After calculation, the ratio of the average length of the carbon fiber to the Dv50 of the silicon-based material is 1.69:1.
[0073] Example 3
[0074] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that in Embodiment 1, except that the Dv50 of the silicon-based material is 12.1. After calculation, the ratio of the average length of the carbon fiber to the Dv50 of the silicon-based material is 0.83:1.
[0075] Example 4
[0076] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that in Example 1, except that the average length of the carbon fiber is 5.43 m. After calculation, the ratio of the average length of the carbon fiber to the Dv50 of the silicon-based material is 0.61:1, and the ratio of the average length of the carbon fiber to the thickness of the first active material layer is 0.2:1.
[0077] Example 5
[0078] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that in Example 1, except that the average length of the carbon fiber is 16.3 m. After calculation, the ratio of the average length of the carbon fiber to the Dv50 of the silicon-based material is 1.83:1, and the ratio of the average length of the carbon fiber to the thickness of the first active material layer is 0.6:1.
[0079] Example 6
[0080] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that in Example 1, except that the average length of the carbon fiber is 5.7 μm. After calculation, the ratio of the average length of the carbon fiber to the Dv50 of the silicon-based material is 0.64:1, and the ratio of the average length of the carbon fiber to the thickness of the first active material layer is 0.21:1.
[0081] Example 7
[0082] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that in Embodiment 1, except that the single fiber diameter of the carbon fiber is 170 and the aspect ratio is 58.8:1.
[0083] Example 8
[0084] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that in Embodiment 1, except that the single fiber diameter of the carbon fiber is 100 nm, and the aspect ratio is 100:1 nm.
[0085] Example 9
[0086] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that in Embodiment 1, except that the single fiber diameter of the carbon fiber is 48 nm and the aspect ratio is 208:1.
[0087] Example 10
[0088] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that in Example 1, except that the first active material includes 20% of silicon-based material and 80% of artificial graphite, the thickness of the first active material layer is 47 μm, and it is calculated that the ratio of the average length of the carbon fiber to the thickness of the first active material layer is 0.21:1.
[0089] Embodiment 11
[0090] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that in Example 1, except that the first active material includes 50% of silicon-based material and 50% of artificial graphite, the thickness of the first active material layer is 18 μm, and it is calculated that the ratio of the average length of the carbon fiber to the thickness of the first active material layer is 0.55:1.
[0091] Example 12
[0092] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that of Example 1, except that the first active material includes 100% silicon-based material, the thickness of the first active material layer is 13 μm, and it is calculated that the ratio of the average length of the carbon fiber to the thickness of the first active material layer is 0.76:1.
[0093] Example 13
[0094] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that in Example 1, except that the first active material includes 20% of silicon-based material and 80% of artificial graphite, the thickness of the first active material layer is 50.3 μm, and it is calculated that the ratio of the average length of the carbon fiber to the thickness of the first active material layer is 0.1981.
[0095] Embodiment 14
[0096] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that in Example 1, except that the first active material includes 100% silicon-based material and 0% artificial graphite, the thickness of the first active material layer is 5.95 μm, and it is calculated that the ratio of the average length of the carbon fiber to the thickness of the first active material layer is 1.681:1.
[0097] Embodiment 15
[0098] The preparation method of the negative electrode sheet provided in this embodiment is basically the same as that in Embodiment 1, except that the single fiber diameter of the carbon fiber is 350 nm, and the aspect ratio is 28.57:1.
[0099] Comparative Example 1
[0100] The method for preparing the negative electrode sheet provided in this comparative example comprises the following steps:
[0101] Artificial graphite, conductive carbon black, styrene-butadiene rubber, sodium carboxymethyl cellulose and polyacrylic acid are mixed in deionized water at a mass ratio of 96.9:0.5:3:1.3:1.3 to obtain an active material slurry, the active material slurry is coated on a copper foil, and roller-dried to obtain a negative electrode sheet.
[0102] Comparative Example 2
[0103] The method for preparing the negative electrode sheet provided in this comparative example comprises the following steps:
[0104] Active material, conductive carbon black, styrene-butadiene rubber, sodium carboxymethyl cellulose and polyacrylic acid are mixed in deionized water at a mass ratio of 91:3:3:1:2 to obtain active material slurry, wherein the active material includes 10% silicon-based material and 90% artificial graphite. The active material slurry is coated on copper foil and roll-dried to obtain a negative electrode sheet.
[0105] Comparative Example 3
[0106] The method for preparing the negative electrode sheet provided in this comparative example comprises the following steps:
[0107] The active material, carbon fiber, styrene-butadiene rubber, sodium carboxymethyl cellulose and polyacrylic acid are mixed in deionized water at a mass ratio of 91:3.5:3:1:1.5 to obtain an active material slurry, wherein the first active material comprises 33% of a silicon-based material and 67% of artificial graphite, and the active material slurry is coated on a copper foil, and rolled and dried to obtain a negative electrode sheet;
[0108] Among them, the Dv50 of the silicon-based material is 8.9μm, the average length of the carbon fiber is 10μm, and the ratio of the average length of the carbon fiber to the Dv50 of the silicon-based material is 1.12:1.
[0109] Comparative Example 4
[0110] The preparation method of the negative electrode sheet provided in this comparative example is basically the same as that in Example 1, except that the Dv50 of the silicon-based material is 13m, the average length of the carbon fiber is 5.1μm, and the ratio of the average length of the carbon fiber to the Dv50 of the silicon-based material is 0.39:1.
[0111] Comparative Example 5
[0112] The preparation method of the negative electrode sheet provided in this comparative example is basically the same as that in Example 1, except that the Dv50 of the silicon-based material is 3.3 m, the average length of the carbon fiber is 5 μm, and the ratio of the average length of the carbon fiber to the Dv50 of the silicon-based material is 1.5:1.
[0113] Comparative Example 6
[0114] The preparation method of the negative electrode sheet provided in this comparative example is basically the same as that in Example 1, except that the Dv50 of the silicon-based material is 3.3 m, the average length of the carbon fiber is 15 μm, and the ratio of the average length of the carbon fiber to the Dv50 of the silicon-based material is 4.5:1.
[0115] Test Example 1
[0116] Positive electrode sheet: Lithium cobalt oxide (LCO), polyvinylidene fluoride (PVDF), and conductive carbon (Super P) are dissolved in N-methylpyrrolidone (NMP) in a mass ratio of 98:1:1, stirred evenly to form a positive electrode slurry, and then evenly coated on the positive electrode current collector aluminum foil. After drying and rolling, the positive electrode sheet is made.
[0117] Electrolyte: The lithium salt used in the electrolyte of the present invention is lithium hexafluorophosphate (LiPF6) with a concentration of 1M, the organic solvent is a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) prepared in a mass ratio of 3:4:3, and the additives are 3wt% fluoroethylene carbonate (FEC) and 1wt% vinylene carbonate.
[0118] The prepared lithium-ion negative electrode sheet, polypropylene porous separator and positive electrode sheet are stacked in sequence, and the battery core is obtained through a winding process. Then, after packaging, liquid injection, formation, sorting and other processes, a soft-pack lithium-ion battery with a conventional winding structure is manufactured.
[0119] Test Example 2
[0120] The negative electrode sheet of Example 1 was subjected to SEM testing, and the SEM images of the carbon fiber and the silicon layer attached to the carbon fiber and the silicon-based material were shown in FIG. Figure 1-4 ,like Figure 1 It can be seen that the carbon fibers are evenly distributed in the first active material layer, and the diameter of the single fiber of the carbon fibers is 100-150 nm; Figure 2 It can be seen that the close contact between carbon fiber and silicon-based material is beneficial to improving the conductivity of the negative electrode sheet; Figure 3 , 4 It can be seen that there is a clear boundary between the first active material layer and the second active material layer, and the first active material layer and the second active material layer can be clearly distinguished.
[0121] Test Example 3
[0122] The lithium ion batteries prepared in the examples and comparative examples were tested for battery performance, and the testing method was as follows:
[0123] DCIR test method: First, let the battery stand at 25℃±2℃ for 10min, then discharge the battery to 3V at 0.2C, let it stand for 10min, then charge it to 4.45V at 0.7C, cutoff current 0.05C, let it stand for 10min, then discharge it to 3V at 0.1C, record the initial capacity as C1, let it stand for 10min, then charge it to 4.45V at 0.7C, cutoff current 0.05C, let it stand for 10min, then discharge it to 0.1C for 10s (200ms sampling), then 1C discharge for 360s (200ms sampling), rest for 15min, repeat the rest for 10min, then discharge at 0.1C for 10s (200ms sampling), then discharge at 1C for 360s (200ms sampling), rest for 15min, until the voltage drops to 3V, in the step of 0.1C discharge for 10s, take the terminal voltage as V0, in the step of 1C discharge for 360s, take the voltage of the initial 5s of discharge as V1, record the DC internal resistance DCIR=(V0-V1) / (1C-0.1C), see Table 1.
[0124] Cycle performance test: the battery was charged to 4.45V at 1C at 25°C, with a cut-off current of 0.2C, and then discharged to 3V at 1C, the discharge capacity was recorded as A1, the charge and discharge steps were repeated 500 times, and the discharge capacity of the 500th cycle was recorded as A2. After 500 5C / 1C cycles, the retention rate η1=A2 / A1*100%, see Table 1.
[0125] Rate charging performance test: First, let the battery stand at 25℃±2℃ for 10min; then discharge the battery at 0.2C to 3V and let it stand for 10min; charge at a certain rate (1C / 1.5C / 2C) with a cut-off current of 0.05C, and record the constant current charging capacity as C1 and the constant current and constant voltage total charging capacity as C2, and let it stand for 10min; discharge at 0.2C to 3V; then the constant current charging ratio = C1 / C2×100%.
[0126] Safety performance test: The battery was charged to 4.45V at 3C at 25°C, with a cut-off current of 0.2C, and then discharged to 3V at 0.5C. After repeating the charge and discharge steps 20 times, the battery was disassembled and the lithium plating of the battery was observed, see Table 1.
[0127] Table 1
[0128]
[0129] Result analysis: With the double-layer coating design, the surface layer doped with silicon-based materials, and the introduction of carbon fibers, the battery impedance is reduced. When the ratio of the average length of the carbon fibers to the Dv50 of the silicon-based materials is in the range of (0.61-1.83):1, it can ensure that the silicon-based materials still have electrical contact after charge and discharge expansion, and the battery impedance and cycle capacity retention rate have obvious advantages. When the Dv50 of the silicon-based material particles is 3.3μm, the cycle stability deteriorates and the battery performance decreases significantly. When the aspect ratio of the carbon fibers is 208:1, the conductivity is significantly reduced and the impedance increases.
[0130] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a current collector, a first active material layer and a second active material layer, wherein the first active material layer is located between the current collector and the second active material layer; the first active material layer comprises a first active material and a conductive agent, wherein the first active material comprises a silicon-based material, and the conductive agent comprises carbon fiber; The ratio of the average length of the carbon fiber to the Dv50 of the silicon-based material is (0.61-1.83):1; the Dv50 of the silicon-based material is 3.5-15 μm.
2. The negative electrode sheet according to claim 1, characterized in that: The ratio of the average length of the carbon fibers to the thickness of the first active material layer is (0.2-1.67):
1.
3. The negative electrode sheet according to claim 1 or 2, characterized in that: The average length of the carbon fiber is 5-20 μm, the diameter of the single fiber is 100-170 nm, and the aspect ratio is (30-200):
1.
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The negative electrode sheet further includes a primer layer, and the primer layer is located between the current collector and the first active material layer.
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The second active material layer includes a second active material including a silicon-based material and graphite.
6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The mass percentage of the carbon fiber in the first active material layer is 0.1-0.5%.
7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The conductive agent further comprises conductive carbon black, and the mass percentage of the conductive carbon black in the first active material layer is 0.5-3%; And / or, the first active material layer further includes a binder, and the mass percentage of the binder in the first active material layer is 3.3-5.3%.
8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: The silicon-based material includes a silicon-carbon composite material, which includes a porous carbon matrix, silicon grains located in the pores of the porous carbon matrix, and a carbon layer located on the surface of the porous carbon matrix.
9. The negative electrode sheet according to claim 8, characterized in that: The carbon layer includes openings arranged corresponding to the pores of the porous carbon matrix.
10. The negative electrode sheet according to any one of claim 8, characterized in that: The specific surface area of the silicon-carbon composite material is 0.5-10m 2 / g; and / or, The particle size Dv50 of the silicon-carbon composite material is 6-15 μm; and / or, The powder resistivity of the silicon-carbon composite material is 0.1-1000Ω·cm; and / or, The silicon content in the silicon-carbon composite material is 30-75%.
11. A battery, characterized in that: The battery comprises the negative electrode sheet according to any one of claims 1 to 10.
